2014
DOI: 10.12693/aphyspola.125.563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nb-Alloying on High-Temperature Oxidation of MoSi2

Abstract: The eects of alloying with 0.5, 1.0, and 2.0 at.% Nb on oxidation resistance of MoSi2 are investigated at temperature range of 1400• C1700• C. Rapid formation of a stable protective layer of silica resulted in a parabolic oxidation rate. The oxide layer thickness and the sample weight increased with increasing oxidation time. Impurities accelerated oxidation rate of MoSi2 only slightly, however, did not aect the rate controlling mechanism for oxidation. There was no correlation between oxidation rate and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…177−179 Several investigations have shown that an oxidation-resistant coating with high reflectivity and low conductivity insulation is a suitable solution for safeguarding a substrate at high temperatures. 104,151,172,173,180,181 Ren et al 171 discovered that Si 2 has excellent hightemperature permanence and oxidation resistance as well as the ability to sustain performance after exposure to air. As a result, Si 2 is widely regarded as the best antioxidation coating material.…”
Section: Co 2hmentioning
confidence: 99%
See 2 more Smart Citations
“…177−179 Several investigations have shown that an oxidation-resistant coating with high reflectivity and low conductivity insulation is a suitable solution for safeguarding a substrate at high temperatures. 104,151,172,173,180,181 Ren et al 171 discovered that Si 2 has excellent hightemperature permanence and oxidation resistance as well as the ability to sustain performance after exposure to air. As a result, Si 2 is widely regarded as the best antioxidation coating material.…”
Section: Co 2hmentioning
confidence: 99%
“…In industries like aerospace engineering, PCP’s low oxidation resistance under high-temperature oxidizing conditions has been shown in several studies to have a significant impact on the material’s service life, making it an urgent obstacle to deploying PCP products in the above harsh settings. As a result, some studies are concentrating their efforts on producing PCP that is resistant to oxidation at high temperatures. Several investigations have shown that an oxidation-resistant coating with high reflectivity and low conductivity insulation is a suitable solution for safeguarding a substrate at high temperatures. ,,,,, …”
Section: Oxidation Mechanisms Of Preceramic Polymer-based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharif and Abbas [60] studied the gravitational perfect fluid charged collapse with cosmological constant in the Friedmann universe model with weak electromagnetic field. Sharif and Ahmad [61]- [64], worked on the spherical symmetric gravitational collapse of perfect fluid withe positive cosmological constant. sharif and Abbas [65], discussed the 5-dimenssional symmetric spherical gravitational collapse with positive cosmological constant in the existence of an electromagnetic field.…”
Section: Introductionmentioning
confidence: 99%